Pengaruh Endorsement Micro-Influencer Instagram Dan Viral Marketing Terhadap Minat Beli Dan Keputusan Pembelian (Studi pada UMKM Makanan di Pasuruan) - Miftahul Huda; Dio Atfianto (Economic Reviews Journal, 2024)
this study aims to measure the direct impact of micro influencer endorsements and viral marketing on purchase decisions, as well as evaluate whether buying interest serves as a mediator in the relationship. This study aims to evaluate the influence of micro influencer endorsements and viral marketing on the purchase decisions of MSME consumers in Pasuruan Regency, as well as the role of buying interest as an intervening variable in the relationship. With the rapid development of social media and the increasing role of influencers in marketing, it is important to understand how micro influencer endorsements and viral marketing strategies influence purchasing decisions. This study uses the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) with the help of SmartPLS 4.0 software to analyze the data obtained from the questionnaire distributed to 116 respondents. The results of the analysis show that micro influencer endorsements and viral marketing have a positive and significant influence on consumer purchase decisions. Micro influencer endorsements were proven to influence purchase decisions with a t-statistic value of 2.894 and a p-value of 0.004, while viral marketing showed a significant influence with a t-statistic value of 4.102 and a p-value of 0.000. Buying interest as an intervening varibael mediated the relationship between micro influencer endorsements and viral marketing on purchase decisions significantly, with p-values of 0.007 and 0.012, respectively.